2021
DOI: 10.1093/milmed/usab497
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise as Treatment for PTSD: A Systematic Review and Meta-Analysis

Abstract: Introduction Post-traumatic stress disorder (PTSD) is a cluster of physical and psychiatric symptoms following military or civilian trauma. The effect of exercise on PTSD symptoms has previously been investigated in several studies. However, it has not been fully determined what type of exercise most impacts PTSD symptoms. The aim of the present study was to systematically review the effects of different types of exercise on PTSD symptom severity and symptoms of coexisting conditions in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 57 publications
4
50
2
2
Order By: Relevance
“…These results were not sufficiently reliable to ensure stable long term benefit. A recent review confirmed these findings showing a small to medium effect (ES: 0.29, 95% CI: 0.10-0.49, P < 0.01) of exercise on PTSD symptom severity whereas a sub-group analysis showed no significant effect of exercise on anxiety and depression severity (Bjorkman and Ekblom, 2021). A previous Cochrane review (Lawrence et al, 2010) attempted to investigate the benefits of exercise in the context of sport and games for PTSD but found only five studies, none of which met the review inclusion criteria, suggesting more research is required to assess the effectiveness of exercise in alleviating symptoms of PTSD.…”
Section: Introductionmentioning
confidence: 88%
“…These results were not sufficiently reliable to ensure stable long term benefit. A recent review confirmed these findings showing a small to medium effect (ES: 0.29, 95% CI: 0.10-0.49, P < 0.01) of exercise on PTSD symptom severity whereas a sub-group analysis showed no significant effect of exercise on anxiety and depression severity (Bjorkman and Ekblom, 2021). A previous Cochrane review (Lawrence et al, 2010) attempted to investigate the benefits of exercise in the context of sport and games for PTSD but found only five studies, none of which met the review inclusion criteria, suggesting more research is required to assess the effectiveness of exercise in alleviating symptoms of PTSD.…”
Section: Introductionmentioning
confidence: 88%
“…Anxiety and stress-related disorders A systematic review and meta-analysis of 13 RCTs investigating the anxiolytic effects of exercise for people with anxiety and related disorders found that exercise had a small, statistically significant effect on decreasing anxiety symptoms compared with control condition (SMD ¼ -0.43, 95% CI ¼ -0.67 to -0.17) [57]. A separate review of 11 studies looking specifically at post traumatic stress disorder (PTSD) identified a positive effect of exercise on PTSD symptom severity compared with nonactive treatment (SMD ¼ 0.46, 95% CI ¼ 0.18-0.74) [58], with evidence of a stronger effect with greater volumes of exercise. Proven strategies to reduce drop out include sessions delivered by an exercise professional and applying autonomous motivation strategies (P < 0.001) [59].…”
Section: Depressive Disordersmentioning
confidence: 99%
“…SRs were published between 2015 and 2022, including 3 to 22 RCTs dated from 1985 to 2020. Eight SRs were supplemented by a meta-analysis [3,[23][24][25][26][27][28][29].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…[3,24,25,[27][28][29][30] and sex ratio from 32.9-100% of women [24,25,[27][28][29][30][31] (concerns only the yoga group in the systematic review of Liu et al [31]). As regards trauma type, the population was heterogeneous with veterans and active military representing about the half of the trauma population in 6 SRs [23][24][25][26][27]31]. In the other 4 SRs, traumas were various in civilian sample population (victims of natural disasters, interpersonal violence, patients with treatment-resistant PTSD, inmates' wives, nurses, patients with multiple sclerosis and PTSD, in-patients in psychiatric unit) [3,28,30,32], and trauma type were not speci ed in one review [29].…”
Section: Participants and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation